Discovery of Ganoderma lucidum triterpenoids as potential inhibitors against Dengue virus NS2B-NS3 protease - Bharadwaj, Shiv (Sci Rep, 2019)
Dengue virus (DENV) infection causes serious health problems in humans for which no drug is currently available. Recently, DENV NS2B-NS3 protease has been proposed as a primary target for anti-dengue drug discovery due to its important role in new virus particle formation by conducting DENV polyprotein cleavage. Triterpenoids from the medicinal fungus Ganoderma lucidum have been suggested as pharmacologically bioactive compounds and tested as anti-viral agents against various viral pathogens including human immunodeficiency virus. However, no reports are available concerning the anti-viral activity of triterpenoids from Ganoderma lucidum against DENV. Therefore, we employed a virtual screening approach to predict the functional triterpenoids from Ganoderma lucidum as potential inhibitors of DENV NS2B-NS3 protease, followed by an in vitro assay. From in silico analysis of twenty-two triterpenoids of Ganoderma lucidum, four triterpenoids, viz. Ganodermanontriol (−6.291 kcal/mol), Lucidumol A (−5.993 kcal/mol), Ganoderic acid C2 (−5.948 kcal/mol) and Ganosporeric acid A (−5.983 kcal/mol) were predicted to be viral protease inhibitors by comparison to reference inhibitor 1,8-Dihydroxy-4,5-dinitroanthraquinone (−5.377 kcal/mol). These results were further studied for binding affinity and stability using the molecular mechanics/generalized Born surface area method and Molecular Dynamics simulations, respectively. Also, in vitro viral infection inhibition suggested that Ganodermanontriol is a potent bioactive triterpenoid.